2011
DOI: 10.3102/0002831211405836
|View full text |Cite
|
Sign up to set email alerts
|

From GED to College

Abstract: Age patterns of secondary certification and college entry differ in complex and surprising ways for traditional graduates and GED recipients. Although GED recipients are less likely to enter college in their late teens, they catch up to traditional graduates in their 20s. Results show that adjusting for differences in the age trajectories of school continuation accounts for a substantial portion of the differences observed between the two groups. Important differences remain, however, in the type of college at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Second, Dr. Thomas transitioned from a general educational diploma (G.E.D.) to a doctorate degree (Ph.D.), which is a rare educational trajectory in academe (Maralani, 2011). Third, Dr. Thomas is a non-traditional student, and as such, faced certain challenges that his traditional student peers did not experience (Chen et al, 2020).…”
Section: Significance Of the Current Topicmentioning
confidence: 99%
“…Second, Dr. Thomas transitioned from a general educational diploma (G.E.D.) to a doctorate degree (Ph.D.), which is a rare educational trajectory in academe (Maralani, 2011). Third, Dr. Thomas is a non-traditional student, and as such, faced certain challenges that his traditional student peers did not experience (Chen et al, 2020).…”
Section: Significance Of the Current Topicmentioning
confidence: 99%
“…Zajacova and Everette (2013), for example, showed that health differentials between GED recipients and HSG were larger among NH Whites than among Hispanics and NH Blacks. Maralani (2011) found that older GED recipients are less likely than their younger peers to subsequently enroll in college. Prins and Kassab (2015) also showed that rural GED recipients were more likely than urban GED recipients to plan to pursue full-time study in a 4-year college.…”
Section: Introductionmentioning
confidence: 98%
“…Based on assumptions about equivalency, most studies have not distinguished between GED recipients and those with a high school diploma (e.g., Torpey, 2018). When disaggregated, however, past studies have yielded overwhelming evidence that GED recipients have less favorable educational, labor market, and health outcomes than do high school graduates (HSG) (e.g., Cameron & Heckman, 1993; Maralani, 2011; Milesi, 2010; Zajacova, 2012). These disparities may be even more pronounced in some subpopulations as the magnitude of the labor market and health disadvantage of GED recipients relative to HSG is not homogenous (Clark & Jaeger, 2006; Prins & Kassab, 2015; Zajacova & Everette, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations